Measurement of the Arctic UTLS composition in presence of clouds using millimetre-wave heterodyne spectroscopy - Castelli, E.; M. Dinelli, B.; Del Bianco, S.; Gerber, D.; Moyna, B. P.; Siddans, R.; Kerridge, B. J.; Cortesi, U. (Atmospheric Measurement Techniques, 2013)
MARSCHALS (Millimetre-wave Airborne Receivers for Spectroscopic CHaracterisation in Atmospheric Limb Sounding) is a limb viewing instrument working in the millimetre and sub-millimetre spectral regions (from 294 to 349 GHz). The scientific rationale of MARSCHALS is the study of the Upper Troposphere and Lower Stratosphere region. In March 2010 MARSCHALS was deployed on-board the M-55 Geophysica stratospheric aircraft during the PREMIER(PRocess Exploration through Measurements of Infrared and millimetre-wave Emitted Radiation)-Ex field campaign. From the campaign base at Kiruna, Sweden, a research flight to investigate the Arctic atmosphere was conducted. For the first time the instrument fully exploited the three spectral bands. In this paper, we present results of the analysis of MARSCHALS measurements acquired during the PREMIER-Ex flight as processed by the Millimetre-wave Atmospheric Retrieval Code. For the second time after the SCOUT-O3 flight in 2005, MARSCHALS measured vertical distributions of temperature, water vapour, ozone and nitric acid over an altitude range of 4 to 24 km. In addition, vertical profiles of carbon monoxide and nitrous oxide were obtained for the first time. The measurements were performed in clear sky conditions and in presence of low and high altitude clouds (that were able to obscure measurements in the middle infrared spectroscopic region) and some information about thick clouds were extracted from the data. The capabilities to derive information on upper tropospheric and lower stratospheric vertical profiles of temperature and minor constituents from millimetre-wave limb sounding observations in the northern polar region are presented and discussed for each of the individual targets. The results of MARSCHALS data analysis contributed to demonstrate the scientific relevance and technical feasibility of millimetre-wave limb-sounding of the UTLS proposed for the ESA Earth Explorer 7 candidate Core Mission PREMIER. PREMIER was not selected at the end of the Earth Explorer 7 evaluation process, but it is still being considered for future launch opportunities.